Recovery of zinc from zinc oxide dust containing multiple metal elements by carbothermal reduction - Lei, Fo-guang; Li, Min-ting; Wei, Chang; Deng, Zhi-gan; Li, Xing-bin; Fan, Gang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
A carbothermal reduction process simulating EAF process is used to handle the zinc oxide dust, and the zinc in the dust can be extracted and recovered efficiently. The crude zinc and lead-tin alloy were obtained finally. The effects of temperature, holding time, and reductant dosage on zinc volatilization rate were investigated, and the “Pelletizing - Calcination-Carbothermic reduction” experiment was conducted. The results found the optimal reduction condition was as follows: the temperature of 1300℃, reductant dosage of 14.04%, and holding time of 120 min. After the calcination at 900℃ for 120 min, the removal rates of fluorine, chlorine, and sulfur in the dust were 98.18%, 96.38% and 28.58% respectively, and the volatilization rate of zinc was 99.83% in the reduction process. The zinc content of the crude zinc was 68.48%.